2006
DOI: 10.1016/j.ica.2006.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Heterobimetallic Fe–Pd and Fe–Pt NCN pincer complexes (NCN=[C6H2(CH2NMe2)2-2,6]−)

Abstract: The meta-diaminoaryl ferrocenes Fc-NCN-H (3) and Fc-C"C-NCN-H (5) (Fc = (g 5 -C 5 H 5 )(g 5 -C 5 H 4 )Fe, NCN-H = C 6 H 3 (CH 2 NMe 2 ) 2 -3,5) can be used as precursors in the preparation of heterobimetallic transition metal complexes of structural type Fc-NCN-MX (NCN = [C 6 H 2 (CH 2 NMe 2 ) 2 -2,6] À ; MX = PdCl (7), PtCl (8), PtI (9)) and Fc-C"C-NCN-MX (MX = PdCl (11), PdI (12), PtCl (13)), respectively. They are accessible by applying different synthesis procedures, including oxidative addition and metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The Pt–Cl distances in 12 and 14 are as expected for NCN-pincer complexes. The Pt–N distances resemble those in other bIB – ,,,, and bPyB – complexes, while N - t Bu complexes have slightly longer Pt–N distances (2.08–2.10 Å), as do Pt II (bAB)X species …”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The Pt–Cl distances in 12 and 14 are as expected for NCN-pincer complexes. The Pt–N distances resemble those in other bIB – ,,,, and bPyB – complexes, while N - t Bu complexes have slightly longer Pt–N distances (2.08–2.10 Å), as do Pt II (bAB)X species …”
Section: Resultsmentioning
confidence: 57%
“…159° indicative of ring strain in the five-membered chelates, as in other NCN-pincer complexes. Pt II (bAB)X and Pt II (bPyB)X , complexes are less strained, with respective N–Pt–N angles of ca. 164 and 161° due to longer C–N distances.…”
Section: Resultsmentioning
confidence: 99%
“…[93][94][95][96][97] Electrochemical properties of the SO 2coordinated (65) and the SO 2 -free compound (60) in solution were studied showing the different redox potentials of Fe(II) in the SO 2 -coordinated and SO 2 free state (Scheme 13). 87 These observations, both by colorimetric and voltametric analysis, revealed that the reduced electron density on Pt(II), caused by the SO 2 coordination, is relayed to the Fe atom of the ferrocene, thus causing a decrease of the Fe redox potential.…”
Section: Dalton Transactions Perspectivementioning
confidence: 95%
“…86 The Fe(II)/Fe(III) oxidation potential for the monometallic specie was 0.03 V, while for complex 58 this was −0.03 V. The set of metallocene-based pincer complexes of type B was expanded following two, different methodologies to obtain the respective CpFeC 5 H 4 (CC) n (NCN)Pd(II)Cl or Pt(II)Cl (n = 0 or 1) derivates, see (Scheme 12). 87,88 The first strategy comprised reaction of the metallocene-pincer precursor with n BuLi followed by a transmetallation reaction. The second strategy involved the synthesis of the iodide precursor from the organolithium complex.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…With PdCl 2 (dppf)/NaOH system, Köcher and colleagues obtained a low yield of (39) by coupling 3,5-(dimethylamino)methyl iodobenzene with ferrocene. Compound (39) was then used for NCN pincer complexes synthesis [37]. Ba(OH) 2 was used as the base by Cammidge and colleagues for the synthesis of face-to-face porphyrin-ferrocene systems [38].…”
Section: Suzuki Couplingmentioning
confidence: 99%